Monoamine depletion by reuptake inhibitors - Hinz, Marty (Dove Medical Press, 2011)
BACKGROUND: Disagreement exists regarding the etiology of cessation of the observed clinical results with administration of reuptake inhibitors. Traditionally, when drug effects wane, it is known as tachyphylaxis. With reuptake inhibitors, the placebo effect is significantly greater than the drug effect in the treatment of depression and attention deficit hyperactivity disorder, leading some to assert that waning of drug effects is placebo relapse, not tachyphylaxis. METHODS: Two groups were retrospectively evaluated. Group 1 was composed of subjects with depression and Group 2 was composed of bariatric subjects treated with reuptake inhibitors for appetite suppression. RESULTS: In Group 1, 200 subjects with depression were treated with citalopram 20 mg per day. A total of 46.5% (n = 93) achieved relief of symptoms (Hamilton-D rating score ≤ 7), 37 (39.8%) of whom experienced recurrence of depression symptoms, at which point an amino acid precursor formula was started. Within 1–5 days, 97.3% (n = 36) experienced relief of depression symptoms. In Group 2, 220 subjects were treated with phentermine 30 mg in the morning and citalopram 20 mg at 4 pm. In this group, 90.0% (n = 198) achieved adequate appetite suppression. The appetite suppression ceased in all 198 subjects within 4–48 days. Administration of an amino acid precursor formula restored appetite suppression in 98.5% (n = 195) of subjects within 1–5 days. CONCLUSION: Reuptake inhibitors do not increase the total number of monoamine molecules in the central nervous system. Their mechanism of action facilitates redistribution of monoamines from one place to another. In the process, conditions are induced that facilitate depletion of monoamines. The “reuptake inhibitor monoamine depletion theory” of this paper offers a novel and unified explanation for the waning of response seen after a reuptake inhibitor is started, independent of a drug or placebo etiology.